The aspartate receptor cytoplasmic domain: in situ chemical analysis of structure, mechanism and dynamics - Bass, Randal B (1999)
BACKGROUND: Site-directed sulfhydryl chemistry and spectroscopy can be used to probe protein structure, mechanism and dynamics in situ. The aspartate receptor of bacterial chemotaxis is representative of a large family of prokaryotic and eukaryotic receptors that regulate histidine kinases in two-component signaling pathways, and has become one of the best characterized transmembrane receptors. We report here the use of cysteine and disulfide scanning to probe the helix-packing architecture of the cytoplasmic domain of the aspartate receptor. RESULTS: A series of designed cysteine pairs have been used to detect proximities between cytoplasmic helices in the full-length, membrane-bound receptor by measurement of disulfide-bond formation rates. Upon mild oxidation, 25 disulfide bonds form rapidly between three specific pairs of helices, whereas other helix pairs yield no detectable disulfide-bond formation. Further constraints on helix packing are provided by 14 disulfide bonds that retain receptor function in an in vitro kinase regulation assay. Of these functional disulfides, seven lock the receptor in the conformation that constitutively stimulates kinase activity (‘lock on’), whereas the remaining seven retain normal kinase regulation. Finally, disulfide-trapping experiments in the absence of bound kinase reveal large-amplitude relative motions of adjacent helices, including helix translations and rotations of up to 19 Å and 180°, respectively. CONCLUSIONS: The 25 rapidly formed and 14 functional disulfide bonds identify helix–helix contacts and theirregister in the full-length, membrane-bound receptor–kinase complex. The results reveal an extended, rather than compact, domain architecture in which the observed helix–helix interactions are best described by a four-helix bundle arrangement. A cluster of six lock-on disulfide bonds pinpoints a region of the subunit interface critical for kinase activation, whereas the signal-retaining disulfides indicate that signal-induced rearrangements of the four-helix bundle are small enough to be accommodated by disulfide-bond flexibility (≤ 1.2 Å). In the absence of bound kinase, helix packing within the cytoplasmic domain is highly dynamic.